Ultrasound-assisted extraction of ergosterol and antioxidant components from mushroom by-products and the attainment of a β-glucan rich residue. (1st December 2020) - Umaña, Mónica; Eim, Valeria; Garau, Carmen; Rosselló, Carmen; Simal, Susana
Graphical abstract: Highlights: Ergosterol, phenolic and antioxidants were extracted from mushroom by-products. Effects of ultrasound and ethanol concentration were evaluated by modeling extraction kinetics. Ergosterol extraction yield was higher on the highest ethanol concentration. Ultrasound improved the ergosterol, phenolic and antioxidants extraction yields. The extraction residues exhibited high β-glucans content. Abstract: Revalorization of mushroom by-product (stalks of A. bisporus ) by extracting its components is proposed. The extraction kinetics at 25 °C of ergosterol, phenolic compounds and antioxidant activity by mechanical agitation (at 130 rpm) and ultrasound assistance (at 182 and 321 W/L) in 70 and 96% v/v ethanol/water solutions during 30 min were evaluated and satisfactorily modelled, using the Weibull model (mean relative error ≤ 7.8%). The effect of the ethanol concentration was high in the ergosterol extraction yield (2 times higher yields in 96% than in 70%) but slight in those of phenolic compounds and antioxidant activity. Ultrasound assistance promoted considerable yield increases (up to 2 times higher in ergosterol, 46% in phenolic compounds and 25% in antioxidant activity) depending on the ethanol concentration and ultrasound power density. The residues after extraction were characterized and constituted a potential source of high value polysaccharides as β-glucans (average 12.2 ± 1.7g/100 g dm).